The Influence of Performance on Service Quality in Dangerous Goods Inspection at Sultan Muhammad Salahuddin Bima Airport - Annisa Nurhikmah; Dhiani Dyahjatmayanti (CV. Rayyan Dwi Bharata, 2023)
Aviation security and safety are very fundamental things that need to be considered by the airport. In terms of aviation security and safety, the role of the Aviation Security (Avsec) unit is certainly not spared. Avsec itself is a very important unit and has a very big role in aviation safety and security. The purpose of this study is to examine how performance influences service quality in the inspection of dangerous goods at Sultan Muhammad Salahuddin Bima Airport. The research method used is descriptive method with a quantitative approach. The data analysis used is the Research Instrument Test and Simple Linear Regression Test. The results of this study indicate that: 1.) Based on the results of the t-test, performance influences service quality significantly. 2.) Based on the coefficient of determination test, it can be concluded that the magnitude of the influence of performance on service quality can be seen in the R Square value indicating a value of 0.771, which means that the independent variable has an influence on the dependent variable of 77.1% while the remaining 22.9% is influenced by other variables outside of the model used.